HLA class I serotypes and cytotoxic T-lymphocyte responses among human immunodeficiency virus-1-uninfected Thai volunteers immunized with ALVAC-HIV in combination with monomeric gp120 or oligomeric gp160 protein boosting - Paris R. (2014)
Antigen-induced cellular immunogenicity may vary between populations due to differences in human leukocyte antigen (HLA) diversity and, hence, may play a critical role in the protection afforded by vaccines. In the setting of two, phase I/II human immunodeficiency virus-1 vaccine trials of a recombinant canarypox prime, and boosting with either recombinant monomeric gp120 or oligomeric gp160, we assessed the association between specific human leukocyte antigen (HLA) class I serotypes and the presence of cytotoxic T-lymphocyte response measured by 51Cr-release assay. HLA class I serotypes A11, A24, A33, B46, and B75 were the most common, present in 10% or more of 245 individuals studied. Forty of 187 (21.4%) Thai adults who received either ALVAC-HIV with gp120 or oligomeric gp160 or ALVAC alone had a precursor cytolytic CD8 T-cell response (pCTL). HLA-B44 was positively and significantly associated with a pCTL response (odds ratio 7.6, 95% CI: 2.7-21.2), whereas B46 was negatively associated but not robust when adjusted for multiple comparisons. Responses to Env proteins accounted for the majority (nine of 11) of pCTL activity among those persons with B44. This HLA class I serotype occurred in 9.4% of participants overall (including the placebo group), less commonly than what is reported from populations of European ancestry. These results strengthen the importance of assessing HLA class I distributions in conjunction with studies of vaccines designed to elicit cellular immunity in different populations.